Psychological Impact of K-Fashion on Tourism Students in Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
In 2003, the influential movement of "Hallyu" was started, and the rapid spread of telenovelaswas the first success of Korean influence in the Philippines. According to Christina Flores, the"hallyu wave" started when Filipinos were deeply influenced by Korea's telenovelas. Based onthe Korean-style fashion in the Philippines (2022) Stated that Filipinos are highly adaptablewhen it comes to different races, cultures, and situations, and they are also susceptible to theinfluence of different cultures from different countries. Korean culture is one of the countriesthat Filipinos have admired, and according to Ahmer Glen M. Et al. (2013), Korean fans havedeveloped not only an interest in Korean novels and Korean pop music but also an increasedaffinity for Korean fashion. An idea has been formed regarding this topic for being unique andinformative about K-trends that influence and affect Filipinos, especially students who areinterested in K-trends that impact tourism students about Korean Fashion. Researchers aim toknow what the Psychological impacts of K-fashion are on Tourism students. In this study,researchers gathered information on the problems encountered by the respondents and thePsychological impact of K-fashion on tourism students.Based on the analysis of data gathering, most of the respondents are from ages 18-20 yearsold, with 177 participants. Also, female Tourism students are the leading respondents of thisstudy, and the year level that got the most respondents is a second-year college with 186respondents. Based on the gathered data, respondents encountered that accessories,clothes, shoes, makeup, and hairstyle can affect a person's confidence, lifestyle, self-satisfaction, and also psychological thinking.On the basis of such findings, researchers recommended that educators conduct seminarsand even orientation, and parents should guide their children to be mindful of following sometrends like K-fashion in order for the students to know what track they are following. Thesupport of the guardians, peers, and parents can make a big impact on the students'psychological thinking. Also, K-fashion is one of the ways to express ourselves, giving self-satisfaction and self-worth that can affect students psychologically. Through the process ofthis paper, the researcher is able to see the real problem that occurred in each situation ofrespondents. There is a need for attention and guidance for those who are facing this kind ofproblem.
Keywords: Mental Health